AI art : machine visions and warped dreams (2020)
The annual Robot Art competition launched by Internet entrepreneur and dating-websites founder Andrew Conru invites ‘visually beautiful’ paintings made by robots. The winners so far include a dot-painted portrait of Albert Einstein, a copy of The Starry Night by Vincent van Gogh that took a robot four hours and fifty minutes to produce (fig. 1) and a series of pictures executed by a programme called CloudPainter. Written by Pindar Van Arman, CloudPainter enables a ‘style transfer’ from the work of an established artist, as a result of which we get pictures which look like they could have been painted by Cézanne or Francis Bacon, but it can also make its own stylistic interventions. In August 2017 Taryn Southern, a self-defined ‘artist/futurist with more than 700 million online views’, launched a song from what she claimed would be the world’s first AI-composed music album.1 Having fed parameters such as mood, tempo and genre into the open source software called Amper, Southern then overlaid the AI-created instrumentation and chord structure with the lyrics and vocal melodies of her own.